If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + 6 = 18 Reorder the terms: 6 + 3g = 18 Solving 6 + 3g = 18 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3g = 18 + -6 Combine like terms: 6 + -6 = 0 0 + 3g = 18 + -6 3g = 18 + -6 Combine like terms: 18 + -6 = 12 3g = 12 Divide each side by '3'. g = 4 Simplifying g = 4
| 0=a^2-20a+96 | | A^2-20a=96 | | 4(h-554)=896 | | 31-3(x+1)=3x | | ((2p)/(p+6))=1 | | -7(u+-5)=-56 | | 5x+10=8x+4 | | 42+7k=21 | | -3.28=2(1.5y-.5) | | x^2-36=-9 | | y=5x-40 | | (q+1)(2q-3)=3 | | 2x+4=3x-10 | | 9(h-84)-5=77 | | (7y)/(7y+7)+(7y-17)/(6y+6)=(6y+1)/(y+1) | | |36-7|=27 | | o/9+13=-3 | | 0/9+13=-3 | | 2/3v+1/6-7/9-5/6 | | 7y/(7y+7)+(7y-17)/(6y+6)=(6y+1)/(y+1) | | (31/5)y=31 | | 5N(N-1)=N+8 | | 12-9x=17-8x | | 31/5y=31 | | |x-5|+2=9 | | |x-5|-2=9 | | u/2-10=-80 | | 3b^2-b-1=0 | | h/2=-70 | | x+7/x+5 | | 4p^2-4p=0 | | -2.3a+16=-5a-38 |